1980
DOI: 10.1111/j.1751-1097.1980.tb03995.x
|View full text |Cite
|
Sign up to set email alerts
|

Photomovement, Pigmentation and Uv‐b Sensitivity in Planaria

Abstract: Four differently pigmented species of planarians were examined for UV-B (i 7 320 280nm) tolerance and ability to detect and avoid CV-B-exposed areas. I t was found that lighter-pigmented species are more UV sensitive and that movement out of the UV-B is directly related to UV sensitivity. Three species showed positioning preference corresponding to their pigmentation; the darker the speclcs, the less avoidance of UV-B. The white (unpigmented) species showed exceptional and very sensitive behavior. IhTRODUCTlOh

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The shape of this survival curve (i.e. the value of Do relative to Dq) is similar to that published for UV-B irradiated D. dorotocephala (Barcelo, 1980). The finding that increasing UV exposures led to lysis at increasingly shorter times may be viewed as U V exposure leading to life shortening (Bond et al, 1965).…”
Section: Germicidal Uv Effectssupporting
confidence: 76%
See 1 more Smart Citation
“…The shape of this survival curve (i.e. the value of Do relative to Dq) is similar to that published for UV-B irradiated D. dorotocephala (Barcelo, 1980). The finding that increasing UV exposures led to lysis at increasingly shorter times may be viewed as U V exposure leading to life shortening (Bond et al, 1965).…”
Section: Germicidal Uv Effectssupporting
confidence: 76%
“…The lethal effects of one photosensitizing compound, eosin yellow, on Dugesia dorotocephala has been reported (Hinrichs, 1924). Other studies have shown that different species of planarians, including D. dorotocephala, are sensitive to very high exposures of germicidal ultraviolet radiation (Merker and Gilbert, 1932;Hinrichs, 1924) and to near-ultraviolet radiation (Spencer and Klein, 1979;Barcelo, 1980). Several species of planarian have been used by Lange (1968aLange ( , 1968b to study the cellular basis of x-radiation lethality.…”
Section: Introductionmentioning
confidence: 99%